2020
DOI: 10.18632/aging.103966
|View full text |Cite
|
Sign up to set email alerts
|

Cross-talk between the ER pathway and the lncRNA MAFG-AS1/miR-339-5p/ CDK2 axis promotes progression of ER+ breast cancer and confers tamoxifen resistance

Abstract: Hormone receptor-positive breast cancer accounts for around 75% of breast cancers. The estrogen receptor pathway promotes tumor progression and endocrine resistance. Recently, the cross-talk between the ER signaling pathway and cell cycle regulation has been identified. It is necessary to determine the underlying molecular mechanisms involved in the ER signaling pathway and find new target genes for prognosis and drug resistance in ER+ breast cancer. In this study, lncRNA MAFG-AS1 was shown to be up-regulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…ER-positive breast cancer accounts for ~70% of breast cancer-related mortalities, and the recurrence rate remains high for several years after surgery ( 5 ). Although anti-estrogen therapy as a classic therapy has reduced the overall mortality of advanced breast cancer by 1/3, the emergence of endocrine resistance affects the survival of patients with ER-positive breast cancer ( 16 ). The present results demonstrated that EPN3 expression was upregulated in breast cancer, and that the OS and RFS of patients with high EPN3 expression were significantly lower than those with low EPN3 expression, thereby confirming that EPN3 may be a risk marker for breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…ER-positive breast cancer accounts for ~70% of breast cancer-related mortalities, and the recurrence rate remains high for several years after surgery ( 5 ). Although anti-estrogen therapy as a classic therapy has reduced the overall mortality of advanced breast cancer by 1/3, the emergence of endocrine resistance affects the survival of patients with ER-positive breast cancer ( 16 ). The present results demonstrated that EPN3 expression was upregulated in breast cancer, and that the OS and RFS of patients with high EPN3 expression were significantly lower than those with low EPN3 expression, thereby confirming that EPN3 may be a risk marker for breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, double luciferase experiments showed that there was a targeted binding relationship between miR-339-5p and Syk, and overexpression of miR-339-5p could negatively regulate the relative expression of Syk proteins and genes. Studies have shown that overexpression of miR-339-5p in prostate cancer [36] and breast cancer [37] decreased cell proliferation activity and caused cell-related in ammatory response. This study showed that the expression level of miR-339-5p in HBZY-1 cells decreased signi cantly, and compared with the model group, overexpression of miR-339-5p signi cantly decreased cell viability, decreased the level of in ammatory factors in cells, and changed the composition of cell cycle.…”
Section: Syk Downregulation Reversed the Effects Of Mir-339-5p On Hbzy-1 Cellsmentioning
confidence: 99%
“…Recently, the lncRNAs BDNF-AS [172], MAFG-AS1 [173] and DILA 1 [174] were also associated with Tam resistance. BDNF-AS overexpression promotes Tam resistance through the BDNF-AS/RNH1/TRIM21/mTOR pathway [172].…”
Section: Long Non-coding Rnas and Tamoxifen Resistancementioning
confidence: 99%
“…BDNF-AS overexpression promotes Tam resistance through the BDNF-AS/RNH1/TRIM21/mTOR pathway [172]. The MAFG-AS1 is upregulated in BC samples [173,[175][176][177] and luminal subtype patients [173]. The MAFG-AS1 knockdown in luminal cell lines, MCF-7 and T47D, decreased cell proliferation, colony formation and promoted cell cycle arrest at G1.…”
Section: Long Non-coding Rnas and Tamoxifen Resistancementioning
confidence: 99%